2008
DOI: 10.1016/j.neubiorev.2007.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral genetic contributions to the study of addiction-related amphetamine effects

Abstract: Amphetamines, including methamphetamine, pose a significant cost to society due to significant numbers of amphetamine-abusing individuals who suffer major health-related consequences. In addition, methamphetamine use is associated with heightened rates of violent and property-related crimes. The current paper reviews the existing literature addressing genetic differences in mice that impact behavioral responses thought to be relevant to the abuse of amphetamine and amphetaminelike drugs. Summarized are studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 304 publications
1
44
0
Order By: Relevance
“…As there are many dosing regimens available in the literature we needed to select one that would be best suited for our study conditions (Imam et al, 2001a, Phillips et al, 2008, Zhu et al, 2006a). A pilot strain survey was conducted using a single 2 mg/kg METH dose to assess whether different OFA behavioral profiles would be elicited across 5 inbred strains (results not shown).…”
Section: 3 Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As there are many dosing regimens available in the literature we needed to select one that would be best suited for our study conditions (Imam et al, 2001a, Phillips et al, 2008, Zhu et al, 2006a). A pilot strain survey was conducted using a single 2 mg/kg METH dose to assess whether different OFA behavioral profiles would be elicited across 5 inbred strains (results not shown).…”
Section: 3 Resultsmentioning
confidence: 99%
“…A continuum of effects ranging from neurotoxicity to acute hyperactivity and behavioral sensitization have been observed. These regimens have spanned from single large doses of 40 mg/kg METH (Imam et al, 2001a) and 4 × 5 mg/kg METH every 2 hours (Zhu et al, 2006a), to acute low doses ranging between 1 and 5 mg/kg METH (Phillips et al, 2008. The use of a 7.5 mg/kg METH challenge 8 days after a single session of 4 × 10 mg/kg METH every 2 hours produced a significant decrease in spontaneous activity, an increase in stereotypic behavior, and a significant decline in the concentration of DA in the caudate nucleus and the nucleus accumbens of rats (Wallace et al, 1999).…”
Section: 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in sensitivity to the locomotor stimulant effect of amphetamines and opioids is heritable (Belknap et al, 1998;Phillips et al, 2008;Gill and Boyle, 2008;Oliverio et al, 1975;Philip et al, 2010). Because epidemiological studies indicate that sensitivity to drug liking in humans can predict an individual's susceptibility to drug abuse (Haertzen et al, 1983;Schuckit, 2009), drug sensitivity and abuse are hypothesized to share a genetic basis.…”
Section: Introductionmentioning
confidence: 99%
“…We used an AIL to study sensitivity to methamphetamine, which is a genetically complex trait that may be useful for identifying genetic factors influencing the subjectively euphoric response to stimulant drugs and susceptibility to drug abuse (Palmer et al 2005;Phillips et al 2008;Bryant et al 2009). For example, a prior study suggested that the gene Casein Kinase 1 Epsilon (Csnk1e) might influence sensitivity to the acute locomotor response to methamphetamine in mice (Palmer et al 2005).…”
mentioning
confidence: 99%